Pollution and Risk Level Assessment of Pollutants in Surface Water Bodies - Giao Thanh Nguyen; Mi Le Thi Diem; Nhien Thi Hong Huynh (Salehan Institute of Higher Education, 2023)
The study was carried out to assess the pollution, impact, and risk level to the surface water environment of pollutants in the water bodies of Soc Trang province, Vietnam. The parameters for evaluating surface water quality and risks included temperature, pH, TSS, DO, BOD, COD, NH4+-N, NO2–N, NO3–N, PO43–P, Cl-, Fet, and coliform. Surface water samples were collected at 35 locations with a frequency of six times (February, April, June, August, October, and December) in 2022. The water quality index (WQI), impact and risk level (risk quotient or RQ, RQ-F), correlation analysis, and principal component analysis (PCA) were utilized in the study. The results show that the surface water has been seriously polluted due to organic matter, nutrients, microorganisms, iron, and salinity. The values of WQI in the dry and rainy seasons fluctuated between bad and very good, indicating that surface water quality is suitable for water transport and other purposes with higher quality requirements. TSS, COD, Fet and coliform have a high impact and risk for the environment in this study area. There were no environmental impacts and risks to NO3–N. Locations with many high-risk pollutants were mainly distributed in residential and coastal areas. The significant negative correlation between the WQI and RQ indicated that the lower the WQI, the higher the environmental risk. The PCA results show that at least six polluting sources affected water quality and caused environmental risks. The results of this study contribute essential and valuable information for improving water quality in the study area through the assessment of environmental impacts and risks.Â Doi: 10.28991/CEJ-2023-09-08-03 Full Text: PDF